2021
DOI: 10.1186/s12879-021-06058-y
|View full text |Cite
|
Sign up to set email alerts
|

Severe pneumonia caused by Parvimonas micra: a case report

Abstract: Background Parvimonas micra (P. micra) is a gram-positive anaerobic coccus that is detected widely on the skin, in the oral mucosa and in the gastrointestinal tract. In certain circumstances, P. micra can cause abdominal abscesses, bacteraemia and other infections. To the best of our knowledge, there have been no case reports describing the biological characteristics of P. micra-related pneumonia. These bacteria do not always multiply in an aerobic organ, such as the lung, and they could be eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…[5][6][7] These reported findings were expected, given the organism is a normal part of gastrointestinal, oral, genital, and potentially skin flora. 2,8 Staphylococcus lugdunensis and Staphylococcus epidermidis, the aerobic infecting agents present in our patient's tear duct culture, are also components of normal skin flora and commonly implicated in nasolacrimal duct infections. 9,10 Because S. lugdunensis, S. epidermidis, and P. micra are components of skin flora, it would be logical to assume skin flora may have entered the tear ducts.…”
Section: Discussionmentioning
confidence: 76%
“…[5][6][7] These reported findings were expected, given the organism is a normal part of gastrointestinal, oral, genital, and potentially skin flora. 2,8 Staphylococcus lugdunensis and Staphylococcus epidermidis, the aerobic infecting agents present in our patient's tear duct culture, are also components of normal skin flora and commonly implicated in nasolacrimal duct infections. 9,10 Because S. lugdunensis, S. epidermidis, and P. micra are components of skin flora, it would be logical to assume skin flora may have entered the tear ducts.…”
Section: Discussionmentioning
confidence: 76%
“…P. micra is an oral opportunistic pathogen that is closely related to periodontitis and other diseases; moreover, it can cause purulent infections of systemic organs [ 30 , 31 ]. Bioinformatics analysis showed that the abundance of P. micra in patients with CRC was significantly higher than that in healthy people [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although both piperacillin–tazobactam and imipenem have some pharmacological effect on anaerobic bacteria, they were very ineffective in treating our patient's infection, and it is presumed that she may have also had a combination of other pathogenic infections. In a report by Yu et al, ( 9 ) a patient was treated with piperacillin–tazobactam and meropenem after lung infection with P. micra , but the initial outcome was unsatisfactory. The infection was finally treated with ornidazole after the pathogenic organism was identified by next-generation sequencing (NGS), and the lung infection was rapidly controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In some reports of infections with P. micra , the final diagnosis is made by reference to the NGS results ( 9 ). NGS is the process of randomly fragmenting and splicing DNA, preparing sequencing libraries, and ultimately obtaining sequence information by performing extension reactions on the tens of thousands of clones in the library and detecting the corresponding signals (the core principle is sequencing while synthesizing).…”
Section: Discussionmentioning
confidence: 99%